The Incidence of Bullying Reports Among Junior and Senior High School Students - Hungo, Melbert (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The rampant problem of bullying among middle and high school students has emotional and academic implications. Addressing this issue can create a safer and more supportive school environment, improve academic achievement, and enforce effective policy. This study analyses the prevalence of bullying among junior and senior high school students. Using a descriptive correlational design and multi-stage sampling technique, researchers collected data from 416 high school students: 184 12th graders and 232 13th graders utilizing the data collection method of a questionnaire, and the data collection instrument was a questionnaire sheet with the Adolescent Peer Relations instrument type. Statistical analysis involved frequency count, arithmetic mean, and chi-square test. The results found that there were significant age-related differences in bullying and victimization patterns among the junior and senior high school students studied. The study concludes that bullying and victimization, exceptionally verbal, are significantly present among junior and senior high school students, with marked age-related variations in their frequency and nature. The implications of this study go beyond schools, impacting the wider society and contributing to a broader understanding and prevention of bullying.